Effect of Underwater Treadmill Gait Training With Water-Jet Resistance on Balance and Gait Ability in Patients With Chronic Stroke: A Randomized Controlled Pilot Trial - Lim, Chae-gil (Frontiers in Neurology, 2020)
Objective: The purpose of this study was to determine the effects of underwater treadmill gait training with water-jet resistance and underwater treadmill gait training with ankle weights on balance and gait abilities in chronic stroke patients. All patient-related research was approved by the Institutional Review Board (IRB) of Gachon University. Methods: Twenty-two inpatients and outpatients with stroke-induced impairments were randomly assigned into 2 groups: an underwater treadmill gait training with water-jet resistance group(n=11) and an underwater treadmill gait training with ankle weights group(n=11). Participants received conventional physical therapy for 30 minutes and underwater treadmill gait training with water-jet resistance or ankle weights for 30 minutes. Intervention was performed 5 days a week for 4 weeks. The Balance System SD was used to assess static and dynamic balance. The GAITRite system was used to assess gait velocity, cadence, step length, stride length, and swing phase. All measurements were performed at the beginning of the study and 4 weeks after the intervention. Results: The water-jet resistance group and ankle weights group showed significant improvement in static balance(P<0.00 vs. P=0.01), dynamic balance(P<0.00 vs. P=0.57), gait velocity(P<0.00 vs. P=0.037), cadence(P<0.00 vs. P=0.001), step length(P<0.00 vs. P=0.003), stride length(P<0.00 vs. P=0.023), and swing phase(P<0.00 vs. P<0.00). However, the static and dynamic balance ability score(P<0.00), gait velocity(P<0.00), cadence(P<0.00), step length(P<0.00), stride length(P<0.00), and swing phase(P=0.023) in the group that received underwater treadmill gait training with water-jet resistance improved more than in the group that received underwater treadmill gait training with ankle weights. Conclusions: Our results demonstrated that underwater treadmill gait training with water-jet resistance is effective in improving static and dynamic balance as well as gait abilities in chronic stroke patients. Thus, training using underwater treadmill gait training with water-jet resistance may be useful in facilitating active rehabilitation in chronic stroke patients.